PENGARUH KNOWLEDGE MANAGEMENT TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KOTA TIDORE KEPULAUAN - Muhammad Asril Arilaha (Jurnal Manajemen Sinergi, 2018)
This research is a quantitative research that aims to obtain empirical evidence about the influence of knowledge management on the performance of employees in the municipal environmental service in the islands. The sampling in this study is overall. The number of samples examined in this study was 43 employees. The data in this study were obtained by collecting primary data in the form of questionnaire. The entire data obtained is processed using SPSS 16 for Windows with multiple linear regression analysis and t test and f test. Based on the results of the study, it is known partially that the three independent variables have a positive effect on the independent variables. While simultaneously the two independent variables also have a positive influence on the dependent variable. Of the three research variables, personal knowledge is a research variable that has the most dominant influence on employee performance.